2005
DOI: 10.1103/physrevlett.95.096104
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Instability inInAs/GaSbSuperlattices due to Interfacial Bonds

Abstract: Synchrotron x-ray diffraction is used to compare the misfit strain and composition in a self-organized nanowire array in an InAs/GaSb superlattice with InSb interfacial bonds to a planar InAs/GaSb superlattice with GaAs interfacial bonds. It is found that the morphological instability that occurs in the nanowire array results from the large misfit strain that the InSb interfacial bonds have in the nanowire array. Based on this result, we propose that tailoring the type of interfacial bonds during the epitaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Recently, the study of the surface instability in biaxially stressed solids has demonstrated that a new diamond morphology is favored when the stress is tensile in one direction and compressive in the orthogonal one (Berger et al, 2003). The effect of morphological change in self-organized nanowire array in InAs/GaSb superlattices due to interfacial bonds has been also studied (Li et al, 2005) as well as the competition as a strain-relief mechanism between misfit dislocations and stress-induced instability of a growing film/vapor interface in the case of an epitaxially stressed thin film on a substrate (Haataja et al, 2002). It can be noticed that the effect of stress on the directional solidification of a planar solid in an external thermal gradient has been carried out and the non-linear evolution of the roughness has been characterized (Cantat et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the study of the surface instability in biaxially stressed solids has demonstrated that a new diamond morphology is favored when the stress is tensile in one direction and compressive in the orthogonal one (Berger et al, 2003). The effect of morphological change in self-organized nanowire array in InAs/GaSb superlattices due to interfacial bonds has been also studied (Li et al, 2005) as well as the competition as a strain-relief mechanism between misfit dislocations and stress-induced instability of a growing film/vapor interface in the case of an epitaxially stressed thin film on a substrate (Haataja et al, 2002). It can be noticed that the effect of stress on the directional solidification of a planar solid in an external thermal gradient has been carried out and the non-linear evolution of the roughness has been characterized (Cantat et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…6,7 In the InAs/GaSb system, which presents a similar problematic, a tensile GaAslike interface has been very recently evidenced by transmission electron microscopy (TEM) 8 The role of In-Sb interfacial bonds in morphological instabilities was also shown by synchrotron X-Ray diffraction. 9 and cross-sectional scanning tunneling microscopy (XSTM). 10 Intermixing at InAs/GaSb interfaces was also studied using Z-contrast microscopy 11,12 and atomic probe tomography.…”
mentioning
confidence: 99%
“…When InSb interfacial bonds were intentionally grown, the InAs layer becomes unstable in a few monolayer thickness, but when GaAs interfacial bonds were grown, the InAs layer remains stable at a much larger thickness. 5,6 In this letter, we attempt to explain the small transition thickness of the aforementioned noncommon anion III-V heterostructures using a simple thermodynamic model following the work of Sasaki et al 2 We show that a large interfacial strain in the noncommon anion systems due to cross bonding at the heterointerface can significantly reduce the transition thickness of a small-strained film, thus providing a possibility of growing self-assembled nanostructures in many semiconductor systems with small lattice mismatch.…”
mentioning
confidence: 98%
“…The nominal "InAs" layers in the superlattice experienced a compressive strain of f = −0.3% due to unintentional incorporation of approximately 12% Sb caused by Sb contamination and/or segregation. 6,14 When the interfacial bonding is chosen to be InSb, it experiences a much larger compressive strain of i = −5.9%. Consequently, according to Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation